2019
DOI: 10.1093/femsec/fiz181
|View full text |Cite
|
Sign up to set email alerts
|

DNA stable isotope probing reveals contrasted activity and phenanthrene-degrading bacteria identity in a gradient of anthropized soils

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous soil organic pollutants. Although PAH-degrading bacteria are present in almost all soils, their selection and enrichment have been shown in historically high PAH contaminated soils. We can wonder if the effectiveness of PAH biodegradation and the PAH-degrading bacterial diversity differ among soils. The stable isotope probing (SIP) technique with 13C-phenanthrene (PHE) as a model PAH was used to: (i) compare for the first time a range of 10 soils with vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 87 publications
2
3
0
Order By: Relevance
“…As already observed in previous studies (e.g. Leflaive et al 2008;Lemmel et al 2019), our results evidenced positive correlations between the intensity of microbial functions and the diversity: cellulose mass losses were significantly and positively related to bacteria OTU numbers, Chao1 richness and Shannon diversity indices. This suggests that only a few bacterial taxa are capable of surviving in environment with highly imbalanced N and P, and these species are probably less efficient in decomposing cellulose under high N:P ratios.…”
Section: Stoichiometric Demand Of Microbial Decomposers For Cellulose...supporting
confidence: 90%
“…As already observed in previous studies (e.g. Leflaive et al 2008;Lemmel et al 2019), our results evidenced positive correlations between the intensity of microbial functions and the diversity: cellulose mass losses were significantly and positively related to bacteria OTU numbers, Chao1 richness and Shannon diversity indices. This suggests that only a few bacterial taxa are capable of surviving in environment with highly imbalanced N and P, and these species are probably less efficient in decomposing cellulose under high N:P ratios.…”
Section: Stoichiometric Demand Of Microbial Decomposers For Cellulose...supporting
confidence: 90%
“…This result also supported to some extent the conclusion in Section 3.1 that some bacteria use intermediate metabolites to grow. The degradation trend of PHE was consistent with the results of community diversity and richness, indicating that the PHE degradation level was positively correlated with bacterial abundance, and that the cooperation between strains led to more efficient PAH degradation [32].…”
Section: Microbial Community Structure Of the Six Samplessupporting
confidence: 82%
“…They are known nitrogen-fixing symbionts mostly found naturally in legumes (Mousavi et al, 2014) and have been identified in anaerobic microbial communities degrading acetate under sulfate-reducing conditions (Bin Hudari et al, 2020), and benzene under nitrate-reducing conditions (Eziuzor et al, 2022), which is the original inoculum for the isolation attempt. ANPR was also found to be the dominant phenanthrene degrader aerobically in gradient anthropized soils (Lemmel et al, 2019). They are likely found in the examples stated above as nitrogen-fixing opportunists due to the presence of nitrate reducers, thereby, contributing to the dissimilatory inorganic nitrogen metabolism…”
Section: Discussionmentioning
confidence: 99%